Behavior of the credit card market in Honduras, from 2021 to 2024 - Flores Huete, Fernando (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To analyze the behavior of the credit card market in Honduras from 2021 to 2024. MATERIAL AND METHOD: This study has a correlational scope, with a non-experimental, cross-sectional, and quantitative design. It uses a non-probability convenience sampling method, focused on the banking sector in Honduras. RESULTS: Credit cards play a fundamental role in the current economic context. It is increasingly necessary for businesses to accept credit card payments, which facilitates transactions both in physical stores and online. This not only stimulates the economy but also offers benefits to users, who can make purchases with funds they do not have available at the time and pay for them at a future date. This financing mechanism allows consumers to take advantage of benefits such as purchases with a 0% interest rate, additional financing, and special discounts. CONCLUSIONS: Conducting this study is crucial for accurately identifying the volume of credit cards in circulation in Honduras, the interest rates applied by financial institutions on credit cards, as well as the behavior of late payments and their impact on the country’s Gross Domestic Product (GDP).